Germline cells in ovarian surface epithelium of mammalians: a promising notion - Celik Onder; Celik Ebru; Turkcuoglu Ilgin; Yilmaz Ercan; Simsek Yavuz; Tiras Bulent (BMC, 2012)
Abstract It is a long held doctrine in reproductive biology that women are born with a finite number of oocytes and there is no oogenesis during the postnatal period. However, recent evidence challenges this by showing the presence of germ line stem cells in the human ovarian surface epithelium (OSE), which can serve as a source of germ cells, and differentiate into oocyte like structures. Postnatal renewal of oocytes may have enormous therapeutic potential especially in women facing the risk of premature ovarian failure idiopathically or iatrogenically after exposure to gonadotoxic chemotherapy and radiation for cancer therapy. This article reviews current knowledge on germ line stem cells in human OSE.